Pengaruh Penambahan Molases sebagai Sumber Glukosa terhadap Karakteristik Fisiko-Kimia Silase Rumput Gajah: The Effect of Molasses Addition as a Glucose Source on the Physic-chemical Characteristics of Elephant Grass Silage - Sadarman Sadarman; Dewi Febrina; Novia Qomariyah; Fungki Firma Mulia; Sri Ramayanti; Satria Trisna Rinaldi; Tri Regina Putri; Danung Nur Adli; Rizki Amalia Nurfitriani; Miftahush Shirothul Haq; Jully Handoko; Alexander Kurniawan Sariyanto Putera (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2023)
This study aimed to examine the molasses addition as a glucose source in the process of elephant grass silage. A completely randomized design consisting of five treatments and five replications was used in this study. The treatments were P1: elephant grass (EG) as control, P2: EG + 2.5% molasses, P3: EG + 5% molasses, P4: EG + 7.5% molasses and P5: EG + 10% molasses based on dry matter. All the treatments were ensiled for 30 days. The parameters included physical quality were aroma, mold growth, texture while the chemical quality parameters were pH, dry matter, dry matter loss, and fleigh value. The data were analyzed for variance and if there were differences between treatments, the Duncan's test was conducted at the 5% level. The results showed that 10% molasses addition had a significant effect (p<0.05) on the physical and chemical qualities of elephant grass silage. The elephant grass silage had a distinctive fermented aroma, no fungi, smooth texture, no clump, and brownish-green color following the molasses color. The pH of elephant grass silage was 3.37-4.52, the silage dry matter was around 27.5%-32.5%, the dry matter loss was around 2.76%-6.73%, while the fleigh value was around 79.2-135. It could be concluded that molasses could be used as a stimulant additive to ensilage elephant grass. Key words: dry matter loss, elephant grass, fungal growth, fleigh value, molasses, pH, silage